10. Photobacterium damsela subsp. piscicida - Varvarigos P. (Diagnostic Manual for the main pathogens in European seabass and Gilthead seabream aquaculture, 2020)
10.1. Aetiology of pasteurellosis (photobacteriosis) 10.2. Clinical diagnosis 10.3. Epizootiology of pasteurellosis (photobacteriosis) 10.4. Sampling 10.4.1. Preparation and shipment of samples from fish 10.5. Diagnostic procedures 10.5.1. Overview 10.5.2. Primary cultivation of bacteria 10.5.3. Screening of pure cultures 10.5.4. Identification of the strain 10.5.4.1. API 10.5.4.2. Slide agglutination 10.5.4.3. Mass spectrometry 10.5.4.4. PCR 10.5.5. In vitro susceptibility testing References Photos